Efeitos protetores do zinco sobre alterações comportamentais e bioquímicas induzidas pelo mercúrio em ratos jovens - Franciscato, Carina (2009)
Mercury is a toxic element that induces biochemical, neurological and behavioral changes, which can persist for a long time after the metal exposure. The contamination by mercury continues being a serious problem of public health in underdeveloped and in development countries, where mines exist for extraction of gold. There was not a treatment totally effective for the cases of exposure or intoxication by the metal. Thus, researches have been developed in the attempt of finding new alternatives for cases of intoxication by mercury. Studies have demonstrated that zinc protects against mercury toxic effects in young rats. The aim of this work was to evaluate the effects of the inorganic mercury exposure on the behavioral performance of rats during and after the exposure, and on biochemical parameters at 24 h e 21 days after the metal exposure. Still, it was investigated the possible preventive effects of zinc on mercury-induced changes. Pups were exposed from 3rd to 7th postnatal day to ZnCl2 (27 mg/kg/day, s.c.) and subsequently to HgCl2 (5 doses of 5 mg/kg/day, s.c.). The rats were submitted to behavioral tasks: negative geotaxis task (3, 5, 7, 9, 11 and 13 days old), tail immersion (13, 20 and 27 days old) and rotarod tests (25 and 30 days old), beaker test (17 to 20 days old) and open field task (30 and 31 days). The animals were daily observed from start of treatment (3 days) until 33 days old to register the number of rats that died. Litters euthanized at 13 days old (24 hours after the last dose of mercury) were used to acetylcholinesterase activity assays and metal levels determination in cerebrum and cerebellum. The animals killed at 33 days old (21 days after the end of mercury exposure) were used to analyze the cerebrum and cerebellum acetylcholinesterase activity, renal and hepatic porphobilinogen-synthase activity, hepatic and renal biochemical parameters, and to determination of metal levels in cerebrum, cerebellum, kidney, liver and blood. Results obtained after 13 days old were divided in two groups of litters that were defined at the end of experimental period (33 days old) as less sensitive rats to mercury and more sensitive rats to mercury in accordance with the recovery of body weight until 33 days old. The mercury exposure caused accumulation of this metal in all analyzed organs of all mercury treated rats. The cerebellum acetylcholinesterase activity from 13 days old rats was decreased. Besides, the mercury-animals of the more sensitive litters to mercury presented impairment in motor function and muscular strength verified in the beaker test, and reduction of the locomotor and exploratory activities in the open field task; decrease in liver and increase in kidney weights, decrease in renal porphobilinogensynthase activity, increase in urea and creatinine levels and decrease of alanine amino transferase activity. This study demonstrates that mercury-induced toxic effects persist for a long time after the end of exposure, and zinc prevents, even that partially, all the alterations induced by mercury. Still, with this work we can also conclude that there are different types of sensibility from the animals to the toxicity of mercury, which can be attributed to the individual susceptibility of each animal, since some animals were so sensitive that died before the end of the experiment; whereas others, in spite of they presented increase of the mercury content in the tissues, they were little sensitive and did not present neither biochemical nor behavioral changes.